DC/TMD Examination Protocol - Yoly Gonzalez; Jason Chwirut; Thomas List; Richard Ohrbach (Association of American Medical Colleges, 2014)
Abstract Introduction This 19½-minute video is an illustration of the standardized clinical examination based on the diagnostic criteria for temporomandibular disorders (DC/TMD). The video was created because of the considerable challenges associated with developing competency in the clinical examination protocol. Typically, multiple learning/training exercises are required in order to achieve mastery. Specifically, this video was conceptualized to address the difficulty that examiners have in integrating their verbal commands, clinical procedures, and responses given by patients. Methods The intended audience includes potential clinical examiners for TMD and dental or medical educators who are teaching the standardized clinical examination for TMD. If implemented in a formal training setting, the video should be used to illustrate how to perform the clinical examination; the instructor/trainer can display the procedures one video segment at a time and follow that with group discussion in order to further explain and to respond to questions. After watching the video, examiner trainees should be paired with a supervisor and practice hands-on implementation of the protocol. If the video is implemented as a self-learning tool, the examiner trainee will benefit from having a training partner. After fully reviewing the video, the two trainees can practice examination procedures on each other, while stepping through the video. Supervision from a trainer is still recommended for final calibration, if possible. Results We have used this video during the last two years as part of both field-testing the examination protocol and field-testing the video as one component of training. The video has been field-tested in both the US and Europe. Feedback from examiner trainees has been incorporated, making the final product the outcome of multiple revisions. Examiner trainees have tended to report a higher level of difficulty, and these issues have been addressed as well. Discussion A major limitation of this work is that it is only presented in English, whereas examiner trainees speak many languages. We are coordinating with several colleagues to translate the clinical protocol into at least 25 languages. It is our goal to eventually incorporate accepted translations into the video in either text or voice formats.